VINOBA BHAVE : A MODEL AND TEACHER OF RENUNCIATION - C. Harris, Iswar (Journal of Dharma, 1980)
For many, Vinoba Bhave will be remembered as an" adopted son" of Mahatma Gandhi. And, for the Indian peasants, he will be praised as a "god who came to distribute the land." 1 Certainly, Vinobaji will be acknowledged in the annals of the Indian people, both as a favourite disciple of Gandhi and as an organizer of the Bhoodan (land gift) Movement. However, in spite of these associations, he needs to be recognized as a yogi - a 20th. century saint __, who followed the path of a sannyasin from an early stage of his life. What needs to be emphasized is that above all, he is a Siidhaka, a seeker of truth, who wishes to complete his Sddhana (search), in the hope of achieving his liberation. Thus, his entire life=-from the time when as a young man, he left his home for the holy city of Banaras, his association with Gandhi, struggle for India’s independence, involvement with Sarvodaya (welfare for all) Movement, and his experiments with "Sukshma" 2 (subtle spiritual power) in the early 1970s is a testimony of a man’s relentless search for God. In this regard, he has paid tributes to the Vedas, Upanisads, Bhagavad Gita, Buddha, Jesus, and Gandhi.